2013
DOI: 10.53879/id.50.02.p0005
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors: A Review

Abstract: HIV protease inhibitors were first invented between 1989 and 1994 by researchers working for the pharmaceutical companies of Hoffmann- La Roche Inc. (in Nutley, New Jersey), Abbott Laboratories and Merck & Co., Inc. HIV protease inhibitors are used in the treatment of patients with AIDS and were considered the first breakthrough in over a decade of AIDS research. Currently, there are five HIV protease inhibitors approved by FDA for the treatment of HIV infection. These drugs work at the final stage of vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Those developed as antivirals over the years include saquinavir, ritonavir, indinavir, nelfinavir, and amprenavir. 11 Many minor protease inhibitors derived from various sources, including plants, organisms, and microbes has been identified. 24 Protease inhibitors contain varying restraint components and target different types of proteases, such as serine, cysteine, aspartyl, and matrix metalloproteinase (MMP).…”
Section: Mechanism Of Action Of Protease Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those developed as antivirals over the years include saquinavir, ritonavir, indinavir, nelfinavir, and amprenavir. 11 Many minor protease inhibitors derived from various sources, including plants, organisms, and microbes has been identified. 24 Protease inhibitors contain varying restraint components and target different types of proteases, such as serine, cysteine, aspartyl, and matrix metalloproteinase (MMP).…”
Section: Mechanism Of Action Of Protease Inhibitorsmentioning
confidence: 99%
“…These can be small molecules, proteins, or peptides that target specific protease enzymes. 11 Numerous metabolites with potential viral protease inhibitory properties have been isolated from various sources, including plants, 12 algae, 13 bacteria, and fungi. 14 Research showed that metabolites derived from Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%